Ideographic Conception of Space: Singularity and Its Importance in the Construction of an Inhabitable World (Revista Rupturas, 2018)
Architecture takes action in the configuration of space, but in spite of the fact that many variables are and have to be quantified and strictly controlled; also as a consequence of it’s direct relationship with human being’s way of living, Architecture is subject to singular phenomena that prevent it from attending archetypal formulas to solve the Dwelling issue. Therefore, this article seeks to recognize the value of life experiences, co-habitation and the narration of significant events, as an essential topic to ensure a human touch in built space, help sensitize our society with it’s environment and the evolution of Architecture itself; that by embracing it’s ideographic contents, manages to integrate in the collective memory and realize that through the construction of places and no-places, directly affects the everyday events of the city and the people who live in it.
Keywords: Dwelling; space ideography; subject-space relationship; no-place; experiential space